A Role for Instructions - Irene Valsecchi (Fondazione Eni Enrico Mattei (FEEM), 2005)
The paper is concerned with instructions as a way of setting premises for subsequent decisions in models of teams à la Marschak-Radner, under information diversification. The paper suggests that instructions can bridge peoples differences in knowledge: they do not require mutual understanding between the sender and the receiver as other forms of communication do. In particular, the knowledge of both the team payoff function and the team organisation can be ordered according to hierarchical ranks. First, the paper shows the equivalence between commands and communication in Marschak and Radner (1972). Second, it derives the requirements in terms of knowledge of the members that follow from given structures of task assignment, information diversification and message flows. Hierarchical ranks are shown to correspond to different degrees of intelligibility of the members with respect to the team operations.
Keywords: D23; L23; M11; 330; Instructions; Hierarchy; Knowledge; Decentralisation; Arbeitsgruppe; Hierarchie; Wissen; Theorie